PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP OPINI AUDIT GOING CONCERN - Vera Nadyani; Yuli Surya Fauzia Pertami (Universitas Sangga Buana, 2025)
The existence of Covid-19 has made all companies, especially the property and real estate company sub-sector, experience a very visible decline, especially on the demand side, so that in the research year there were several companies that received a going concern audit opinion. This study aims to determine the effect of liquidity and solvency on going concern audit opinion. The population in this study were 85 property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. Sampling was carried out using purposive sampling technique and resulted in 20 companies with a total of 100 data samples / observations. This study uses quantitative research methods with descriptive approaches and associative analysis. The analysis method used is descriptive statistical analysis and logistic regression analysis using SPSS Statistic 26 software. The results of the study indicate that partially liquidity has a significant effect on going concern audit opinion and solvency has no effect on going concern audit opinion. While simultaneously liquidity and solvency have a significant effect on going concern audit opinion. The Coefficient of Determination shows that the independent variable has an influence of 23%.